Indonesian Authors in Global Islamic Banking Research: A Bibliometric Analysis - ridhooka rizqi, ilham; relanda putra, trischa (LP2M IAIN Palopo, 2025)
This study aims to identify contemporary trends, assess the role and standing of Indonesian authors within the global research framework, and analyze the disparities in our comprehension of the evolution of Islamic finance, including prevalent topics and areas requiring further investigation. This study uses bibliometric analysis of data from academic publications found in the Scopus database to investigate the literature on Islamic finance. The results of this analysis show how publications have changed by nation, organization, author, and the connections between journals, and research areas. The number of academic publications on Indonesian Islamic banking by Scopus-indexed Indonesian authors fluctuated between 2010 and 2024, peaking in 2016 and 2022. In addition to the growing usage of terms like Islamic, Indonesian, and banking, the main study subjects from 2017 to 2023 will be banks, performance, evidence, and finance.